Size and Cycle : An Essay on the Structure of Biology - Bonner, John Tyler (Book collections on Project MUSE., 2016)
A discussion of life cycles and individual size in organisms, and of the relationships between the two, and of their conjoint role in evolution. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.